2020
DOI: 10.20961/carakatani.v35i2.35713
|View full text |Cite
|
Sign up to set email alerts
|

The Potensial of Fusarium sp. and Chaetomium sp. as Biological Control Agents of Five Broad-Leaf Weeds

Abstract: Weeds are a major problem in crop cultivation, either in food crops, horticulture, plantations or forests and cause a decrease in the quality and quantity of production. Weed biocontrol, especially by using plant pathogenic fungi, has received attention but is still lacking in application. The purpose of this study was to determine the potential of <em>Fusarium</em> sp. and <em>Chaetomium</em> sp. as biological control agents against five broad-leaf weeds (<em>Asystasia gangetica&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This shows that in the same plant genus, pathogenic fungi can cause disease in one species, but in other species, pathogenic fungi may not necessarily cause disease (Li et al, 2020). Soesanto et al (2020) reported that Chaetomium sp. can cause disease in weeds, but in cultivated plants Chaetomium sp.…”
Section: Disease Symptommentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that in the same plant genus, pathogenic fungi can cause disease in one species, but in other species, pathogenic fungi may not necessarily cause disease (Li et al, 2020). Soesanto et al (2020) reported that Chaetomium sp. can cause disease in weeds, but in cultivated plants Chaetomium sp.…”
Section: Disease Symptommentioning
confidence: 99%
“…(Soesanto et al, 2021). The three weed pathogenic fungi have been tested on several weeds (Soesanto et al, 2020(Soesanto et al, , 2021. Pathogenic fungi cause high damage to weeds (Mira et al, 2021) and affect weed growth in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal isolates of F. oxysporum, Curvularia sp., and Chaetomium sp. (Soesanto et al, 2018(Soesanto et al, , 2020 were prepared on Potato Dextrose Agar media for 7 days at room temperature. Next, five agar cork drills (5 mm diameter) containing pathogenic fungi were put into a 500 ml Erlenmeyer flask containing Potato Dextrose Broth (PDB).…”
Section: Preparation Of Weed Pathogenic Fungimentioning
confidence: 99%
“…Weed pathogenic fungi, i.e., Chaetomium sp., Fusarium sp., and Curvularia lunata, were prepared in PDA (Soesanto et al 2020). Furthermore, the three weed pathogenic fungi were propagated using three liquid media, i.e., Potato Dextrose Broth (PDB), rice washing water, and tofu liquid waste, which were shaken out at 150 rpm (Daiki) at room temperature for 7 days.…”
Section: Preparation Of Weed Pathogenic Fungal Isolatesmentioning
confidence: 99%